KARAWITAN WAYANG WALISANGA SEBAGAI MANIFESTASI MUSIK SENI ISLAMI - Wasiran . (SELONDING, 2012)
The Walisanga’s puppet performance has its uniqueness which is able to distinguish to another type of puppet performance. One of the uniqueness is the song or the piece. In accordance with the identity, song, and the lyric has to be appropriate with the Islamic religion. This phenomenon is very interesting to investigate as long as the song appropriate with the Islamic value. In order to understand the object, this investigation uses gamelan music knowledge and hermeneutic. The result is a synergy correlation between gamelan music pieces with the Islamic religious proselytizing using gamelan music performance, as a form of specific Javanese culture to the Indonesian society which is majority consist of Moslems community. Keywords: Karawitan, Walisanga Puppets, Islamic Music